PROBLEMATIZING SOCIAL SCIENTIFIC DISCOURSE OF COLONIALISM ON POST-COLONIAL THEORIES - Ruhi Can Alkin (European Scientific Journal, ESJ, 2014)
In this study, historical and sociological discourse of colonialist movements will be critically analyzed by referring post-colonial theories. In doing so, it is proposed to shed light on the process of colonialism, its reason, consequences and impact on colonialized territories in the light of social science discipline. In order to generate a systematic study, the issue problematized will be examined in an historical approach. That is why, the text will include some sub-titles that might show the development and status of colonialist discourse in social science (and specifically sociology) literature. After that, some deconstructive theories on colonialist discourse will be mentioned in consideration of new/contrary arguments on race and culture. At the end of the study, Orientalizm as one of the well-known colonialist discourse of Western dominance will be discussed. This paper doesn’t propose to give detailed information on colonialist movements in an historical context. It, rather, proposes to underline the Western view of the World and movements on colonialized countries encouraged by these view. That is why, throughout the stud, modern Western theories will be attributed to colonialist approaches and actions.